Elucidating the structure and dynamics of CO ad-layers on MgO surfaces. Issue 48 (5th November 2019) - Maul, Jefferson; Spoto, Giuseppe; Mino, Lorenzo; Erba, Alessandro
Abstract : The structure and dynamics of the ordered CO ad-layer on MgO surfaces is determined by combining theoretical quantum-mechanical calculations and experimental infrared spectroscopic measurements. Abstract : The combination of quantum-mechanical simulations and infrared absorption spectroscopy measurements provides a clear picture for a long standing puzzle in surface science: the actual structure and vibrational dynamics of the low-temperature ordered CO monolayer adsorbed on (001) MgO surfaces. The equilibrium structure of the commensurate (4 × 2) adsorbed phase consists of three CO molecules per primitive cell (surface coverage of 75%) located at two inequivalent sites: one molecule seats upright on top of a Mg site while two molecules, tilted off the normal to the surface, are symmetrically positioned relative to the upright one with anti-parallel projections on the surface. This configuration, long believed to be incompatible with measured polarization infrared spectra, is shown to reproduce all observed spectral features, including a new, unexpected one: the vanishing anharmonicity of CO stretching modes in the monolayer.